2004
DOI: 10.1111/j.1365-2842.2004.01269.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral parafunctions and association with symptoms of temporomandibular disorders in Japanese university students

Abstract: We examined whether oral parafunctions are associated with symptoms of temporomandibular disorders (TMD) in 3557 Japanese university students, aged between 18 and 26 years. Participants completed a questionnaire regarding various oral parafunctions and subjective symptoms related to TMD, and underwent a dental examination. The prevalence of temporomandibular joint (TMJ) noise, TMJ pain and impaired mouth opening was 41.7, 16.0 and 16.3%, respectively. The most prevalent parafunction was sleeping on one side (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
64
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 16 publications
15
64
3
6
Order By: Relevance
“…6,15,30,31,40,41 And while Choi and Choung Moon 6 have reported that bruxism cannot be a direct risk factor for TMD, there are reports showing that clenching was more often associated with TMJ symptoms and clinically relevant to the occurrence of the same, increasing the risk of manifestation of TMJ pain and noise and losses in the mouth opening. 17,22,24,29,44 Therefore, a likely association between bruxism and TMD signs/symptoms supports the theory that repetitive loads on the masticatory system can cause functional disorders. 3 Regarding the positive correlation observed between age and severity of signs and symptoms, it should be considered that only 24 sample subjects had more than 40 years.…”
Section: Habitssupporting
confidence: 56%
“…6,15,30,31,40,41 And while Choi and Choung Moon 6 have reported that bruxism cannot be a direct risk factor for TMD, there are reports showing that clenching was more often associated with TMJ symptoms and clinically relevant to the occurrence of the same, increasing the risk of manifestation of TMJ pain and noise and losses in the mouth opening. 17,22,24,29,44 Therefore, a likely association between bruxism and TMD signs/symptoms supports the theory that repetitive loads on the masticatory system can cause functional disorders. 3 Regarding the positive correlation observed between age and severity of signs and symptoms, it should be considered that only 24 sample subjects had more than 40 years.…”
Section: Habitssupporting
confidence: 56%
“…22,23 It was reported to cause TMD in the form of masticatory muscle dysfunction, pain, and clicking. 24,25 Even though no study was conducted to investigate the relationship between the level of severity of TMD and khat chewing, previous studies demonstrated the relation between unilateral chewing habits and TMD as mentioned by Nilsson, 26 Chauhan et al, 27 Miyake et al, 28 and Casanova-Rosado et al 29 Our result showed no differences between khat and nonkhat chewers; this could be explained by the short period of the chewing habit among the involved students in the present study. Even though this study provided some information regarding the prevalence and severity of TMDs among Saudi university students in a particular area, longterm clinical studies are advised to be conducted in this region.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 No research has investigated the relationship between the level of severity of TMD and khat chewing, although some studies have demonstrated the relation between unilateral chewing habits and TMD. [26][27][28][29] Even though there are scores of universities in KSA, only a few studies have been conducted to measure the prevalence of TMD among their students. 7,10,13 Many studies in other universities concluded that TMD is higher among medical students than other disciplines.…”
Section: 5005/jp-journals-10024-1982mentioning
confidence: 99%
“…A variety of factors contribute to TMD, including parafunction (bruxism and teeth clenching), trauma, mental disorders, poor health and nutrition, and hormonal factors (6)(7)(8)(9)(10)(11)26). It is likely that various risk factors for TMD overlap, making the etiology complicated.…”
Section: Prevalence and Etiology Of Tmd In Individuals Using A Vdt Atmentioning
confidence: 99%
“…Formerly, TMD was thought to occur as a result of malocclusion (5). However, though more recently several different influences, including parafunction (bruxism and teeth clenching), and traumatic, anatomical, psychological, hormonal (i.e., estrogen), and hereditary factors have been reported to be involved in its development (6)(7)(8)(9)(10)(11). Among the risk factors for TMD, psychological aspects are thought to be important for understanding its etiology.…”
Section: Introductionmentioning
confidence: 99%